Media Pembelajaran Online untuk Mendukung Belajar Pada Stebis Islam Darussalam - Tri Oktarina (Universitas Bumigora, 2020)
This research was conducted to develop a learning system in STEBIS Islam Darussalam. STEBIS Islam Darussalam is one of the private universities in South Sumatra Province, Lempuing District, Ogan Komering Ilir Regency. The learning system in STEBIS Islam Darussalam which is currently being implemented face-to-face meetings in the classroom with several ways of delivering material include presentations, discussions, and questions and answers directly. The media used in learning are physical books, projectors, and blackboards. As for the weaknesses of this system, if there are students who are not familiar with the material and miss the material it will be difficult to study or repeat the material because they have to find book sources that are used as reference material. Students who want to relearn the material must also bring the material in physical form, it is also quite difficult if it cannot be carried anywhere. The solution to overcome these problems is the need for the development and addition of online learning media such as online modules. The online module is presented in an electronic format and accessed online. The purpose of developing online learning media is to facilitate students in learning and repeating material, because learning media can be accessed online. The method used in system development is the waterfall method with several stages of requirements (requirements analysis), system design (system design), coding (coding) & testing (testing), Program Implementation, maintenance. This research produced online learning media at STEBIS Islam Darussalam.